O trabalho educativo do enfermeiro na estratégia saúde da família no âmbito da 10ª Regional de Saúde do Paraná - Roecker, Simone (2010)
Health education in providing care to the population, in the scope of the Family Health Strategy (FHS), it was established as an essential activity to all multi-professional staff, especially to the nurse. And such activity involves, not only the teaching of healthy habits for life, but also, the prepare the individual to seek better life conditions, encouraging him to exercise his autonomy and social control. Before exposed, the aim of this study was to understand the nurses' perception about the educational work developed in the FHS, in the scope of the 10th Regional Health of the State of Parana. This is a descriptive exploratory study, with qualitative research. The data were collected from 20 nurses that work in the FHS in the scope of the 10th Regional Health, through semi-structured interviews, during the month of April 2010 and submitted to the categorical content analysis (Bardin). The results show that nurses understand the concept of health education and recognize its relevance, especially concerning to primary health care, however, the educational actions achieved by them are still below the recommended by the FHS and, mostly, tied to the traditional model of health education. The educational actions are conducted as much in individual as collective scope, and are, almost exclusively, tied to programs and policies of the Ministry of Health, in other words, toward to activities that are established and already are imposed by the Regional and Departments Health of the municipalities which integrate this Regional Health. It was observed that sporadically differentiated educational activities are developed, through the nurse's observation on the needs of the population, but without her active participation. They are faced several obstacles in the realization of educational practice due to the unawareness of pedagogical trends, of methodologies and lack of systematization on the actions that lead the make educative of nurses. Besides these obstacles, the nurses face several difficulties in the health education development referent to users, to members of the multi-professional team, to managers and to insufficiency of physical, material and financial resources. It was possible to observe that, through difficulties experienced, the professionals seek different alternatives to overcome them and suggest changes aiming improvement to the population care, mainly, regarding to educational work. Therefore, it was emphasized the need to clarify better the objectives of the FHS related with the health education for professionals working in this care model, establishing a process of training and continuing education, besides develop means to systematize the health education since the professional formation. Thus, health education must not be considerate just as another activity to be achieved at FHS, but as a practice that sustain and reorients all primary care, aim to promote the health of individuals, families and community.